An Abdominal Presentation of Churg-Strauss Syndrome. (20th July 2010) - Rees, J. R. E.; Burgess, P.
Abstract : Churg-Strauss syndrome is a small and medium vessel vasculitis that is also known as allergic granulomatous angiitis. It most commonly presents with an asthma like symptoms. It was first described in Mount Siani Hospital, New York in 1951 by Jacob Churg and Lotte Stauss and was recognised after the study of a series of 13 patients who had asthma, eosinophilia, granulomatous inflammation necrotising systemic vasculitis and necrotising glomerulonephritis. We describe a case of Churg-Strauss syndrome presenting with abdominal pain and later during the hospital admission a mono-neuritis multiplex syndrome affecting the lower limbs. The patient presented in such an atypical fashion with abdominal signs and symptoms that they required laparotomy and the diagnosis was made after histological examination of tissue taken at the time of surgery. Treatment with immunosuppression and aggressive rehabilitation achieved a progressive recovery which continued on discharge from hospital.